“Iso standardization of colors or in the process of recycling in schools” - Lupera Navarrete, Joffre Olmedo (Revista Universidad de Guayaquil, 2012)
In a few educational institutions in the city of Guayaquil applies colors in their recycling containers (bins) for different recyclable solid waste, trash and we consider that every minute we produce in our daily live within our schools, homes or workplace, with this process we reduce the high environmental pollution, waste generated in the natural environment of our community or city.This article discusses the application of standardized color in the recycling process, organic and inorganic provenance (composition and chemical bonding, use and degradation time) of different recyclable waste, generated in all educational institutions: Organic , paper and cardboard, plastics, glass, biomedical and others because they were never considered in international standards, allowing us to demonstrate how in some educational institutions, recreation centers and businesses locally, nationally and countries, applying recycling being used irresponsibly for many recyclables colors that brings confusion and disorder, creating different problems of classification and disposal because they are not consistent with the colors that people know in their community and country.
Keywords: Color Standardization of Recycling; Training; Classification Problems; International Standards; Solid Waste Recycling